Male reproductive toxicity induced by Microcystin-leucine-arginine (MC-LR). (30th April 2022) - Xu, Guanghui; Luo, Yang; Xu, Dihui; Ma, Yuhan; Chen, Yabing; Han, Xiaodong
Abstract: Microcystin-LR (MC-LR) has been identified to pose an increasing threat to the male reproductive system in vivo and in vitro studies with the objects like mammal animals, amphibians, aquatic organisms, etc. This review demonstrates the latest research advances of the male reproductive toxicity induced by MC-LR in detail, which mainly consists of two aspects, namely pathological injuries to testis and prostate, as well as the endocrine disruption. Apart from the direct toxicity to the male reproductive system, we also underline the transgenerational reproductive toxicity that prenatal exposure may pass on to male offspring. This review also demonstrates the interactive effects between MC-LR and other compounds, including synergistic effects with some toxicants and antagonistic effects with some medicine or chemical modification. In terms of the mechanisms of MC-LR-induced toxicity, we mainly focus on the epigenetic modification and non-coding RNAs (ncRNAs)-related mechanisms which have provided a new perspective. Graphical abstract: Image 1 Highlights: Microcystin-leucine-arginine induces male reproductive toxicity, including pathological injuries and endocrine disruption. Transgenerational reproductive effects on male offspring are investigated. Synergistic and antagonistic effects between Microcystin-leucine-arginine and other substances help toxicity-management. Epigenetic modifications and non-coding RNAs-related investigations may provide novel insights into mechanisms.